1986
DOI: 10.1007/bf03179366
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of a tropical lepidopteranCatopsilia crocale (Pieridae)

Abstract: Extensive field observations were undertaken to study the population dynamics of the larvae of Catopsilia crocale in the Madurai Kamaraj University campus during the years 1980-81 and 1981-82. Though oligophagous, C. crocale adopted 'monophagic strategy' for oviposition and larval feeding. Seasonal changes in the nitrogen content of the food Cassia alata leaf influenced the pupal/adult weight and oviposition. Commencement of rain triggered the reproductive activity and continued precipitation facilitated maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, leaf water content of some trees (e.g. Cassia alata; Christopher 1983) is as high as that of some forbs and Catopsilia crocale feeding on C. alata leaf displays as high Ase as those feeding on forbs containing 85% water content. It is therefore suggested that there is a need for the collection of more information on this aspect before the observation of Scriber could be confirmed or contradicted.…”
Section: Discussionmentioning
confidence: 98%
“…However, leaf water content of some trees (e.g. Cassia alata; Christopher 1983) is as high as that of some forbs and Catopsilia crocale feeding on C. alata leaf displays as high Ase as those feeding on forbs containing 85% water content. It is therefore suggested that there is a need for the collection of more information on this aspect before the observation of Scriber could be confirmed or contradicted.…”
Section: Discussionmentioning
confidence: 98%
“…The three early stages and adults can be found in their natural habitat all year. Rainfall appears to be the most essential component in A. merione merione Cramer, as it is in Catopsilia crocale [8] and Catopsilia pyranthe [9]. Precipitation during the North-West monsoon most likely influenced host plant reproduction.…”
Section: Resultsmentioning
confidence: 99%